State of art review wáter pollution control benefits and Costs - Unger, Samuel G (Office of Research and Monitoring / Washington, 1973)
The state of art survey presented attempts to classify and assess Benefit cost analyses applied to wáter resources management problems in light of relatively recent serious concerns involving enviromental quality issues. Rather piece-meal analyses have been completed. Traditional benefit cost analyses have in corporated little regarding either costs or benefits which fall outside market oriented systems.